DNA Barcoding Reveals High Cryptic Diversity in the North Eurasian Moina Species (Crustacea: Cladocera) - Bekker, Eugeniya I.; Karabanov, Dmitry P.; Galimov, Yan R.; Kotov, Alexey A. (PloS one, 2016)
Species of the genus Moina Baird (Cladocera: Moinidae) often dominate freshwater crustacean communities in temporary water bodies. Several species of Moina are used as food for fish larvae in aquaculture, as bioindicators in toxicological studies, and as common subjects for physiological studies. The aim of this paper is to estimate biodiversity of Moina in northern Eurasia using the standard DNA barcoding approach based on the cytochrome c oxidase subunit I (COI) gene. We analysed 160 newly obtained and 157 existing COI sequences, and found evidence for 21 phylogroups of Moina, some of which were detected here for the first time. Our study confirmed the opinion that the actual species diversity of cladocerans is several times higher than is presently accepted. Our results also indicated that Moina has the second richest species diversity among the cladoceran genera (with only Daphnia O. F. Mueller having a greater diversity of species). Our study strongly supports division of Moina into two faunistic groups: European-Western Siberian and Eastern Siberian-Far Eastern, with a transitional zone at the Yenisey River basin (Eastern Siberia). Here, we refrain from taxonomic descriptions of new species, as this requires a thorough morphological and taxonomic study for each putative taxon.